Effects of variation in resource acquisition during different stages of the life cycle on life‐history traits and trade‐offs in a burying beetle. (27th October 2018) - Richardson, Jon; Smiseth, Per T.
Abstract: Individual variation in resource acquisition should have consequences for life‐history traits and trade‐offs between them because such variation determines how many resources can be allocated to different life‐history functions, such as growth, survival and reproduction. Since resource acquisition can vary across an individual's life cycle, the consequences for life‐history traits and trade‐offs may depend on when during the life cycle resources are limited. We tested for differential and/or interactive effects of variation in resource acquisition in the burying beetle Nicrophorus vespilloides . We designed an experiment in which individuals acquired high or low amounts of resources across three stages of the life cycle: larval development, prior to breeding and the onset of breeding in a fully crossed design. Resource acquisition during larval development and prior to breeding affected egg size and offspring survival, respectively. Meanwhile, resource acquisition at the onset of breeding affected size and number of both eggs and offspring. In addition, there were interactive effects between resource acquisition at different stages on egg size and offspring survival. However, only when females acquired few resources at the onset of breeding was there evidence for a trade‐off between offspring size and number. Our results demonstrate that individual variation in resource acquisition during different stages of the life cycle has important consequences for life‐history traits but limited effects on trade‐offs. This suggests that in species that acquire a fixed‐sized resource at the onset of breeding, the size of this resource has larger effects on life‐history trade‐offs than resources acquired at earlier stages.